Investigations Regarding the Addition of ZnO and Li2O-TiO2 to Phosphate-Tellurite Glasses: Structural, Chemical, and Mechanical Properties - Elisa, Mihail; Iordache, Ștefan-Marian; Iordache, Ana-Maria; Stefan, Constantina Raluca; Vasiliu, Ileana Cristina; Cristea, Daniel; Ursuțiu, Doru; Samoilă, Cornel; Sava, Bogdan Alexandru; Boroica, Lucica; Dinca, Marius Cătălin; Filip, Ana Violeta; et al. (MDPI AG, 2022)
Phosphate and tellurite glasses can be used in optics, optoelectronics, magneto-optics, and nuclear and medical fields. Two series of phosphate-tellurite glasses, (50-x)ZnO-10Al2O3-40P2O5-xTeO2 and (40-x)Li2O-10Al2O3-5TiO2-45P2O5-xTeO2 (x = 5, 10), were synthesized by a non-conventional wet-route, and the mechanical properties as key performance measures for their application in optoelectronics were investigated. X-ray Diffraction (XRD) measurements revealed the vitreous nature of the investigated materials. Instrumented indentation tests allowed the calculation of hardness (H) and Young’s modulus (E) using the Oliver and Pharr model. The influence of increasing the TeO2 content, as well as the substitution of ZnO by Li2O-TiO2, on the variation of hardness, Young’s modulus, penetration depth (PD), and fracture toughness (FT) was evaluated in both series. As a general trend, there is a decrease in the hardness and Young’s modulus with increasing penetration depth. The addition of Li2O and TiO2 instead of ZnO leads to improved hardness and elastic modulus values. Regarding the H/E ratio, it was found that the samples with lower TeO2 content should be significantly more crack-resistant compared to the higher TeO2 content samples. The H3/E2 ratio, being lower than 0.01, revealed a poor resistance of these glasses to plastic deformation. At the same time, a decrease of the fracture toughness with increasing TeO2 content was noticed for each glass series. Based on dilatometry measurements, the thermal expansion coefficient as well as the characteristic temperatures of the glasses were measured. Field Emission Scanning Electron Microscopy-Energy Dispersive X-ray analysis (FESEM-EDX) revealed a uniform distribution of the elements in the bulk samples. The mechanical properties of these vitreous materials are important in relation to their application as magneto-optical Faraday rotators in laser cavities.
Keywords: mechanical properties; phosphate glass; scanning electron microscopy; tellurite glass; thermal expansion coefficient